Synthesis, reactions and applications of pyranotriazolopyrimidines - El-Wahab, Ashraf Hassan Fekry Abd; Radini, Ibrahim Ali; Mohamed, Hany Mostafa (European Journal of Chemistry, 2014)
This review deals with synthesis, reactions and their applications of pyrano triazolo pyrimidines. The main purpose of this review is present a survey of literatures on the reactivity of amino imino derivatives and carboxylic acid derivatives. Some of these reactions have been applied successfully to the synthesis of biological important compounds.